Accelerated Denaturation of Hemoglobin and the Antimalarial Action of Chloroquine - Fitch, Coy D. (American Society for Microbiology, 2006)
To study the antimalarial action of chloroquine, normal mouse erythrocytes were used as surrogates for erythrocytoid bodies. These bodies form in the endosomes of intraerythrocytic malaria parasites as they feed on their host and consist of erythrocyte cytoplasm enclosed in a vestige of the erythrocyte membrane. In suspensions of normal erythrocytes or lysates (equivalent to 5 μl of erythrocytes per ml in each case), hemoglobin underwent denaturation when it was incubated at 38°C in 150 mM sodium acetate (pH 5). It is reasonable to assume that the same phenomenon occurs in acidic endosomes. Addition of 100 μM chloroquine to the incubation mixture caused the rate of hemoglobin denaturation to double to 40 nanomoles per hour per ml of packed erythrocytes. This effect required the presence of erythrocyte stroma and was inhibited by reducing the temperature to 24°C or increasing the pH to 6. We propose that the primary antimalarial action of chloroquine is to bind to ferriprotoporphyrin IX (FP) and remove it from oxidized hemoglobin, thus producing toxic FP-chloroquine complexes and an excess of denatured globin. Furthermore, we suggest that these substances inhibit endosomal maturation and thereby cause hemoglobin accumulation in immature endosomes and masking of the lipids needed for FP dimerization. The term “masking” is used to signify that unsaturated lipids are present in parasitized erythrocytes but are specifically unavailable to promote FP dimerization.